The moss-specific transcription factor PpERF24 positively modulates immunity against fungal pathogens in Physcomitrium patens - Reboledo, Guillermo; Agorio, Astrid; Vignale, Lucía; Alvarez, Alfonso; Ponce De León, Inés (Frontiers in Plant Science, 2022)
APETALA2/Ethylene-responsive factors (AP2/ERF) transcription factors have greatly expanded in land plants compared to algae. In angiosperms, AP2/ERFs play important regulatory functions in plant defenses against pathogens and abiotic stress by controlling the expression of target genes. In the moss Physcomitrium patens, a high number of members of the ERF family are induced during pathogen infection, suggesting that they are important regulators in bryophyte immunity. In the current study, we analyzed a P. patens pathogen-inducible ERF family member designated as PpERF24. Orthologs of PpERF24 were only found in other mosses, while they were absent in the bryophytes Marchantia polymorpha and Anthoceros agrestis, the vascular plant Selaginella moellendorffii and angiosperms. We show that PpERF24 belongs to a moss-specific clade with distinctive amino acids features in the AP2 domain that binds to the DNA. Interestingly, all P. patens members of the PpERF24 subclade are induced by fungal pathogens. The function of PpERF24 during plant immunity was assessed by an overexpression approach and transcriptomic analysis. Overexpressing lines showed increased defenses to infection by the fungal pathogens Botrytis cinerea and Colletotrichum gloeosporioides evidenced by reduced cellular damage and fungal biomass compared to wild type plants, Transcriptomic and RT-qPCR analysis revealed that PpERF24 positively regulates the expression levels of defense genes involved in transcriptional regulation, phenylpropanoid and jasmonate pathways, oxidative burst and pathogenesis-related genes. These findings give novel insights into potential mechanism by which PpERF24 increases plant defenses against several pathogens by regulating important players in plant immunity.